1928
DOI: 10.1080/00378941.1928.10836296
|View full text |Cite
|
Sign up to set email alerts
|

Quelques Graminées nouvelles pour la flore de l'Indo-Chine

Abstract: Les matériaux récoltés au cours de ces dernières années par M. Pételot, professeur à l'Ecole supérieure d'Agriculture de Hanoï, permettent de faire quelques nouvelles additions à la Flore de l'Indo-Chine. Ces plantes, recueillies en grande partie dans la région septentrionale montagneuse du Tonkin, sont pour la plupart des espèces qui ont déjà été signalées dans les montagnes du nord de l'Inde, et du sud de la Chine, principalement du Yunnan.Parmi les échantillons envoyés au Muséum par M. Pételot, Downloaded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Prob. We also confirmed the identification of Vietnamese C. tripilifera made by Camus (1928). The study of the overall distribution of these three Vietnamese species of Calamagrostis revealed the first record of C. tripilifera from the Daba Mts in northern Chongqing Municipality in southwest China, and the first record of C. extremiorientalis from Japan's Bonin Islands (also known as the Ogasawara Islands).…”
Section: In Checklist Of Plant Species In Vietnamsupporting
confidence: 64%
See 4 more Smart Citations
“…Prob. We also confirmed the identification of Vietnamese C. tripilifera made by Camus (1928). The study of the overall distribution of these three Vietnamese species of Calamagrostis revealed the first record of C. tripilifera from the Daba Mts in northern Chongqing Municipality in southwest China, and the first record of C. extremiorientalis from Japan's Bonin Islands (also known as the Ogasawara Islands).…”
Section: In Checklist Of Plant Species In Vietnamsupporting
confidence: 64%
“…In the present paper, the misidentified species previously reported as C. elatior (Camus 1928;Schmid 1958;Khoi & Đo 2005) is correctly named C. extremiorientalis (Tzvel.) Prob.…”
Section: In Checklist Of Plant Species In Vietnammentioning
confidence: 85%
See 3 more Smart Citations